Negative electrode material and preparation method and application thereof
By adjusting the content relationship between silicon material, binder and conductive agent in the negative electrode material of lithium-ion batteries, the expansion problem of elemental silicon negative electrode material is solved, and a negative electrode sheet with high capacity and excellent circulation performance is achieved.
Patent Information
- Application Number
- CN202311082683.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-02-25
AI Technical Summary
The existing elemental silicon negative electrode materials expand due to volume effects in lithium-ion batteries, affecting the circulation performance.
By designing the relationship between the content of silicon material and the content of binder and conductive agent, a negative electrode material containing silicon material, binder and conductive agent was prepared to ensure that the negative electrode sheet has a high capacity and reduce the expansion rate.
The high capacity and excellent circulation performance of the negative electrode sheet are achieved, and performance degradation caused by expansion is avoided.
Smart Images

Figure BDA0004423559420000121 
Figure HDA0004423559430000011
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a negative electrode material and a preparation method and application thereof. Background Art
[0002] The structure of commercialized electrochemical devices such as lithium-ion batteries is mainly composed of positive electrode sheets, negative electrode sheets, separators, electrolytes and shells. With the continuous development of battery cell technology and changes in terminal demand, the demand for high-energy and fast-charging cells is becoming more and more clear. In order to achieve high energy density and fast charging capabilities, the current mainstream route is to increase the surface capacity of the negative electrode. The current negative electrode material is mainly graphite, but due to the low theoretical capacity (372mAh / g), it limits the further improvement of the gram capacity of the negative electrode sheet.
[0003] Silicon anode materials have a theoretical capacity of about 10 times that of current commercial graphite anode materials, and are gradually moving from laboratory research and development to commercial applications. However, existing single-element silicon anode materials have a serious volume effect during the lithium insertion and extraction process, with a volume change rate of about 300%. The expansion problem of silicon-containing anode plates will cause excessive plate rebound and loss of conductive network between particles during the cyclic charge and discharge process, thereby affecting the cycle performance of electrochemical devices such as lithium-ion batteries.
[0004] Therefore, how to increase the gram capacity of the negative electrode and avoid expansion, and thereby improve the cycle performance of electrochemical devices such as lithium-ion batteries, is an issue that needs to be urgently addressed in the industry. Summary of the invention
[0005] The present application aims to solve one of the technical problems in the related art at least to some extent.
[0006] In view of this, one purpose of the present application is to propose a negative electrode material, which contains a silicon material, a binder and a conductive agent, and by designing the relationship between the content of the silicon material and the content of the binder and the conductive agent, it can be ensured that when the negative electrode material is used for the negative electrode plate, it has a higher gram capacity and can reduce the expansion rate of the negative electrode plate, and has excellent cycle performance.
[0007] Another object of the present application is to provide a method for preparing a negative electrode material.
[0008] Another object of the present application is to provide a negative electrode plate.
[0009] Another object of the present application is to provide an electrochemical device.
[0010] Yet another object of the present application is to provide a vehicle.
[0011] To achieve the above-mentioned object, the first embodiment of the present application proposes a negative electrode material, comprising an active substance, a binder and a conductive agent; the active substance comprises a silicon material, and the mass content of the silicon material in the negative electrode material is less than 20%;
[0012] The mass content of the binder in the negative electrode material is 0.01-5wt%;
[0013] The mass content of the conductive agent in the negative electrode material is 0-3wt%.
[0014] In some embodiments, the amount of the silicon material and the amount of the binder conform to the relationship of formula (1), and the amount of the silicon material and the amount of the conductive agent conform to the relationship of formula (2):
[0015] (-0.0112Csi 2 +0.3836Csi+0.1813)<Cn<(-0.0006Csi 2 +0.0555Csi+0.0106)(1),
[0016] (-0.0003Csi 2 +0.0159Csi+0.0065)<Cm<(-6*10 -5 C 2 +0.0035Csi+0.0014)(2), Wherein, Csi is the content of silicon material in the negative electrode material, wt %; Cn is the content of binder in the negative electrode material, wt %; Cm is the content of conductive agent in the negative electrode material, wt %.
[0017] In some embodiments, the content of the active substance in the negative electrode material is 92-99 wt %.
[0018] In some embodiments, the silicon material includes at least one of silicon oxide, pre-lithium silicon oxide, pre-magnesium silicon oxide, and silicon-carbon material.
[0019] In some embodiments, the active material further comprises graphite.
[0020] In some embodiments, the binder includes at least one of hydroxymethyl cellulose salt, styrene-butadiene rubber, polyacrylic acid, and polyacrylate.
[0021] In other embodiments, the binder is polyacrylic acid and / or polyacrylate.
[0022] In some other embodiments, the binder is a mixture of hydroxymethyl cellulose salt, styrene butadiene rubber, polyacrylic acid and / or polyacrylic acid salt, wherein the mass ratio of hydroxymethyl cellulose salt, styrene butadiene rubber, polyacrylic acid and / or polyacrylic acid salt is (0.1-2): (0.1-3): (0.1-5).
[0023] In some embodiments, the hydroxymethylcellulose salt includes at least one of sodium hydroxymethylcellulose and lithium hydroxymethylcellulose.
[0024] In some embodiments, the polyacrylate includes at least one of lithium polyacrylate, sodium polyacrylate, potassium polyacrylate, and ammonium polyacrylate.
[0025] In some embodiments, the conductive agent includes at least one of carbon nanotubes, carbon black, vapor-grown carbon fibers, and graphene.
[0026] In some embodiments, the conductive agent is a mixture of carbon black and carbon nanotubes, and the mass ratio of the carbon black to the carbon nanotubes is (0.1-3): (0.1-2).
[0027] In some embodiments, the carbon nanotubes include at least one of multi-walled carbon nanotubes, few-walled carbon nanotubes, and single-walled carbon nanotubes.
[0028] To achieve the above object, a second embodiment of the present application provides a method for preparing a negative electrode material, comprising:
[0029] The active material, the binder and the conductive agent are mixed to obtain the negative electrode material.
[0030] To achieve the above-mentioned purpose, the third aspect of the present application provides a negative electrode plate, including the negative electrode material of the embodiment of the present application, or the negative electrode material prepared by the preparation method of the embodiment of the present application.
[0031] In some embodiments, the compaction density of the negative electrode material is 1.3-1.75 g / cm 3 .
[0032] To achieve the above-mentioned purpose, the fourth aspect of the present application proposes an electrochemical device, including the negative electrode material of the embodiment of the present application, or the negative electrode material prepared by the preparation method of the embodiment of the present application, or the negative electrode plate of the embodiment of the present application.
[0033] To achieve the above-mentioned objectives, the fifth aspect embodiment of the present application proposes a vehicle, including the negative electrode material of the embodiment of the present application, or the negative electrode material prepared by the preparation method of the embodiment of the present application, or the negative electrode plate of the embodiment of the present application, or the electrochemical device of the embodiment of the present application.
[0034] The negative electrode material of the embodiment of the present application can at least bring the following beneficial effects:
[0035] It contains silicon material, binder and conductive agent, and by designing the relationship between the content of silicon material and the content of binder and conductive agent, it can ensure that when the negative electrode material is used for the negative electrode plate, it has both high gram capacity and low expansion rate of the negative electrode plate, and has excellent cycle performance.
[0036] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0038] Figure 1 A schematic diagram of the structure of a negative electrode plate is shown in an exemplary embodiment of the present application.
[0039] Reference numerals:
[0040] 1-silicon material; 2-graphite; 3-binder; 4-carbon black; 5-carbon nanotubes; 6-current collector. DETAILED DESCRIPTION
[0041] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.
[0042] Throughout the application, the disclosure of numerical ranges includes all values within the entire range and disclosure of further subdivided ranges, including endpoints and subranges given within those ranges.
[0043] In the application, the raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be produced through commercial channels or known methods; the methods involved, unless otherwise specified, are all conventional methods.
[0044] The inventors found that the expansion of silicon-containing negative electrode sheets is directly related to the silicon content in the negative electrode material. At the same time, the conductive network is directly related to the conductive agent. The right amount of binder can maintain a good bonding effect between the active material particles, which is beneficial to the improvement of the cycle performance. Therefore, there is a potential relationship between the silicon content, the amount of binder and the amount of conductive agent. The design makes the silicon content and the content of binder and conductive agent meet a certain relationship, which can form different negative electrode materials and then constitute different negative electrode sheet structures. These negative electrode sheet structures have both high surface capacity and can reduce the expansion rate of the negative electrode sheet, and have excellent cycle performance. In addition, mixing graphite and other materials with silicon materials in the negative electrode material and optimizing the negative electrode compaction density can also further improve the cycle performance.
[0045] The negative electrode material of the embodiment of the present application includes an active substance, a binder and a conductive agent; the active substance includes a silicon material, and the mass content of the silicon material in the negative electrode material is less than 20%; the mass content of the binder in the negative electrode material is 0.01-5wt%; the mass content of the conductive agent in the negative electrode material is 0-3wt%.
[0046] As a non-limiting example, the content of silicon material in the negative electrode material is 0.01wt%, 1wt%, 2.5wt%, 5wt%, 7.5wt%, 10wt%, 12.5wt%, 15wt%, 17.5wt% or 19.9wt%, etc. When the content of silicon material in the negative electrode material is within the above range, the energy density of the battery cell can be taken into account while maintaining good cycle performance of the silicon material; when it exceeds the above range, the silicon material causes an increase in the total interface side reaction and deteriorates the cycle performance.
[0047] In some embodiments, the silicon material includes but is not limited to at least one of silicon oxide, pre-lithium silicon oxide, pre-magnesium silicon oxide, silicon carbon material, and the like.
[0048] As a non-limiting example, the silicon-carbon material includes, but is not limited to, at least one of silicon-carbon material, SiNPs-amorphous carbon, SiNPs-graphite, and the like.
[0049] It should be noted that in the embodiments of the present application, pre-lithium silicon oxide and pre-magnesium silicon oxide are both materials that can be obtained through commercial channels.
[0050] In some embodiments, the content of the active substance in the negative electrode material is 92-99wt%, including but not limited to 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt% or 99wt%, etc. When the content of the active substance in the negative electrode material is within the above range, the energy density of the battery cell can be taken into account while maintaining good cycle performance; less than 92wt%, the side reaction of the interface of the inactive substance increases, which is not conducive to the cycle performance; more than 99wt%, the bonding failure between the active substance particles will result in serious loss of the negative electrode material and deterioration of the cycle performance.
[0051] In some embodiments, the content of the binder in the negative electrode material includes but is not limited to 0.01wt%, 0.1wt%, 0.3wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, etc. When the content of the binder in the negative electrode material is within the above range, a good bonding effect between the active material particles can be maintained, which is beneficial to the improvement of the cycle performance; when it is less than 0.01wt%, the bonding between the active material particles will fail, resulting in serious loss of the negative electrode material and deterioration of the cycle performance; when it is greater than 5wt%, the binder will increase the interface side reaction, which is not conducive to the cycle performance.
[0052] In some embodiments, the content of the conductive agent in the negative electrode material is 0-3wt%. As a non-limiting example, the content of the conductive agent in the negative electrode material includes but is not limited to 0.01wt%, 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt% or 3wt%. When the content of the conductive agent in the negative electrode material is within the above range, a good conductive network between the active material particles can be maintained, which is beneficial to the improvement of the cycle performance; when it is greater than 3wt%, the conductive agent causes an increase in the interface side reaction, which is not conducive to the cycle performance.
[0053] Preferably, in some embodiments, the amount of silicon material used and the amount of binder used conform to the relationship of formula (1), and the amount of silicon material used and the amount of conductive agent used conform to the relationship of formula (2):
[0054] (-0.0112Csi 2 +0.3846Csi+0.1813)<Cn<(-0.0006Csi 2 +0.0555Csi+0.0106)(1),
[0055] (-0.0003Csi 2 +0.0159Csi+0.0065)<Cm<(-6*10 -5 C 2+0.0035Csi+0.0014)(2), Wherein, Csi is the content of silicon material in the negative electrode material, wt %; Cn is the content of binder in the negative electrode material, wt %; Cm is the content of conductive agent in the negative electrode material, wt %.
[0056] In some embodiments, the active material further includes graphite. Mixing graphite and silicon materials in the negative electrode material can further improve the cycle performance.
[0057] As a non-limiting example, graphite includes but is not limited to at least one of natural graphite, artificial graphite, composite graphite, mesophase carbon microbeads, metal oxide materials (TiO2-B, MoO, CoO, etc.), and the like.
[0058] It should be noted that in the embodiments of the present application, the negative electrode material may contain other active substances, such as soft carbon, hard carbon, graphene, etc., in addition to silicon material and graphite.
[0059] As a possible example, the active material is composed of silicon material and graphite, wherein the content of the silicon material is less than 20wt% and the rest is graphite.
[0060] In some embodiments, the binder includes, but is not limited to, at least one of hydroxymethyl cellulose salt, styrene butadiene rubber (SBR), polyacrylic acid (PAA), polyacrylate, and the like.
[0061] As a non-limiting example, the hydroxymethylcellulose salt includes, but is not limited to, at least one of sodium hydroxymethylcellulose, lithium hydroxymethylcellulose, and the like.
[0062] As a non-limiting example, the polyacrylate includes, but is not limited to, at least one of lithium polyacrylate, sodium polyacrylate, potassium polyacrylate, ammonium polyacrylate, and the like.
[0063] As a possible example, the binder is polyacrylic acid, or polyacrylic acid salt, or a mixture of polyacrylic acid and polyacrylic acid salt. When the binder is a mixture of polyacrylic acid and polyacrylic acid salt, the mixing mass ratio of polyacrylic acid and polyacrylic acid salt is not limited, for example, it can be 1:1.
[0064] As another possible example, the binder is a mixture of hydroxymethyl cellulose salt, styrene butadiene rubber, polyacrylic acid or / and polyacrylic acid salt, wherein the mass ratio of hydroxymethyl cellulose salt, styrene butadiene rubber, polyacrylic acid or / and polyacrylic acid salt is (0.1-2):(0.1-3):(0.1-5). It should be noted that in this mass ratio, polyacrylic acid or / and polyacrylic acid salt is calculated as a whole with hydroxymethyl cellulose salt and styrene butadiene rubber. As a non-limiting example, the mass ratio of hydroxymethyl cellulose salt, styrene butadiene rubber, polyacrylic acid or / and polyacrylic acid salt includes but is not limited to 1:1:1, 0.1:3:5, 0.1:3:0.1, 2:3:5, 2:0.1:0.1, 2:0.1:5 or 1:1.5:2.5, etc.
[0065] In some embodiments, the conductive agent includes but is not limited to at least one of carbon nanotubes, carbon black, vapor-grown carbon fibers, graphene, and the like.
[0066] As a possible example, the conductive agent is carbon nanotubes. When the mass content of the conductive agent in the negative electrode material satisfies the relationship of the above formula (2), a good conductive network between the active material particles can be better maintained, which is more conducive to improving the cycle performance.
[0067] As another possible example, the conductive agent is a mixture of carbon black and carbon nanotubes, and the mass ratio of carbon black to carbon nanotubes is (0.1-3):(0.1-2), including but not limited to 0.5:1, 1:0.5, 1:1, 2:0.25, 3:0.1 or 3:2, etc.
[0068] In some embodiments, carbon nanotubes (CNTs) include, but are not limited to, at least one of multi-walled carbon nanotubes, few-walled carbon nanotubes, single-walled carbon nanotubes, and the like.
[0069] The negative electrode material of the embodiment of the present application contains silicon material, a binder and a conductive agent. By designing the relationship between the content of the silicon material and the content of the binder and the conductive agent, it can be ensured that when the negative electrode material is used for the negative electrode plate, it has a high gram capacity, does not expand seriously, and has excellent cycle performance.
[0070] Specifically, in the embodiments of the present application, when the content of silicon material in the negative electrode material is less than 20wt%, there are two main factors affecting the cycle performance of the silicon-containing material: one is the contact between particles, which is maintained by a binder; the other is the maintenance of the conductive network between particles, which is achieved by a conductive agent.
[0071] The method for preparing the negative electrode material of the embodiment of the present application comprises the following steps: mixing the above-mentioned active material, the above-mentioned binder and the above-mentioned conductive agent to obtain the negative electrode material.
[0072] In some embodiments, the mixing is performed by stirring.
[0073] As a possible example, the method for preparing the negative electrode material of the embodiment of the present application includes the following steps: performing a first stirring and a second stirring on the active material, the binder and the conductive agent at one time to mix the materials uniformly to obtain the negative electrode material.
[0074] In some embodiments, the first stirring speed is greater than the second stirring speed. The purpose of this arrangement is to fully physically mix the negative electrode materials and dissolve the binder.
[0075] In some embodiments, the first stirring speed is 1000-1400rpm / min, and the first stirring time is 1-3h. As a non-limiting example, the first stirring speed includes but is not limited to 1000rpm / min, 1100rpm / min, 1200rpm / min, 1300rpm / min or 1400rpm / min, etc.; the first stirring time includes but is not limited to 1h, 1.5h, 2h, 2.5h or 3h, etc.
[0076] In some embodiments, the second stirring speed is 400-600rpm / min, and the second stirring time is 0.1-2h. As a non-limiting example, the second stirring speed includes but is not limited to 400rpm / min, 450rpm / min, 500rpm / min, 550rpm / min or 600rpm / min, etc.; the second stirring time includes but is not limited to 0.1h, 0.5h, 1h, 1.5h or 2h, etc.
[0077] The negative electrode plate of the embodiment of the present application includes the negative electrode material of the embodiment of the present application, or the negative electrode material prepared by the preparation method of the negative electrode material of the embodiment of the present application.
[0078] In some embodiments, Figure 1 (the conductive agent is carbon nanotubes), the negative electrode plate also includes a negative electrode current collector. Among them, the negative electrode current collector can be selected to include copper or any other suitable conductive metal foil (such as solid or mesh or covered foil) known to those skilled in the art, a metal grid or screen, or a porous metal. In some variations, the surface of the negative electrode current collector may include a metal foil that has been surface treated (e.g., carbon coated and / or etched).
[0079] In some embodiments, the compaction density of the negative electrode material in the negative electrode sheet is 1.3-1.75 g / cm 3 , including but not limited to 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3, 1.7g / cm 3 or 1.75g / cm 3 The compaction density of the negative electrode material in the negative electrode sheet is within the above range, which can maintain a good conductive network between the active material particles and is conducive to improving the cycle performance; less than 1.3g / cm 3 , the contact between active material particles is poor, and the cycle deteriorates; if it is higher than 1.75g / cm 3 , the active material will expand after lithium insertion, resulting in poor bonding deformation, poor contact between particles, and cycle degradation.
[0080] As a possible example, the method for preparing the negative electrode sheet of the embodiment of the present application includes the following steps:
[0081] The negative electrode material is added to the negative electrode solvent, dispersed at a speed of 2300-2700rpm / min for 70-110s three times, and the slurry is placed for 0.1-3h after homogenization to obtain the negative electrode slurry; then the negative electrode slurry is coated on the negative electrode current collector, and then rolled and dried to obtain the negative electrode sheet. During the rolling process, the surface density and compaction density of the negative electrode sheet are controlled to reach the preset target value.
[0082] It should be noted that, in the preparation process of the above-mentioned negative electrode sheet, when the placement time exceeds 30 minutes, the negative electrode slurry needs to be dispersed again at a rotation speed of 2300-2700 rpm / min before coating.
[0083] In some embodiments, the preset target value of the surface density of the negative electrode material is 1.5-2.5 g / cm 2 The preset target value of compaction density is the above compaction density (1.3-1.75g / cm 3 As a non-limiting example, the preset value of the surface density includes but is not limited to 1.5 g / cm 2 , 1.7g / cm 2 , 1.9g / cm 2 , 2.1g / cm 2 , 2.3g / cm 2 or 2.5g / cm 2 wait.
[0084] The electrochemical device of the embodiment of the present application includes the negative electrode material of the embodiment of the present application, or the negative electrode material prepared by the preparation method of the embodiment of the present application, or the negative electrode plate of the embodiment of the present application.
[0085] In some embodiments, the electrochemical device may include, but is not limited to, a secondary battery such as a lithium-ion battery, a capacitor, etc. The secondary battery is not limited to a button battery, a soft-pack battery, etc.
[0086] In some embodiments, the electrochemical device further includes a positive electrode sheet, a separator, and an electrolyte.
[0087] In some embodiments, the positive electrode sheet includes a positive electrode material, and the positive electrode material includes at least one of a positive electrode active material, a positive electrode conductive agent, a positive electrode binder, etc. It should be noted that the present application has no particular restrictions on the specific selection of the positive electrode active material, the positive electrode conductive agent, the positive electrode binder, etc. As a non-limiting example, the positive electrode active material includes but is not limited to one or more of lithium cobalt oxide, lithium manganate, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, fluorolithium vanadium phosphate, lithium titanate, lithium nickel cobalt manganate, and lithium nickel cobalt aluminum oxide; the positive electrode conductive agent includes but is not limited to one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60, and carbon nanotubes; the positive electrode binder includes but is not limited to one or more of polyvinylidene fluoride (PVDF), sodium alginate, sodium carboxymethyl cellulose, and polyacrylic acid.
[0088] In some embodiments, the positive electrode sheet also includes a positive current collector, which may be selected to include aluminum or any other suitable conductive metal foil (such as solid or mesh or covered foil) known to those skilled in the art, a metal grid or screen, or a porous metal. In some variations, the surface of the positive current collector may include a metal foil that has been surface treated (e.g., carbon coated and / or etched).
[0089] In some embodiments, the diaphragm includes but is not limited to polyethylene (PE), polypropylene (PP), polytetrafluoroethylene-based polyolefin (PO) diaphragms, polyester films (such as polyethylene terephthalate (PET) films), cellulose films, polyimide films (PI), polyamide films (PA), spandex or aramid films, woven membranes, non-woven membranes (non-woven fabrics), microporous membranes, composite membranes, diaphragm paper, rolled membranes or spun membranes, etc.
[0090] In some embodiments, the electrolyte includes but is not limited to 1 mol / L LiPF6 solution, etc. The solvent is a non-aqueous organic solvent, including but not limited to at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), etc.; the additive includes but is not limited to at least one of fluoroethylene carbonate (FEC), vinylene carbonate (VC), etc.
[0091] The vehicle of the embodiment of the present application includes the negative electrode material of the embodiment of the present application, or the negative electrode material prepared by the preparation method of the embodiment of the present application, or the negative electrode plate of the embodiment of the present application, or the electrochemical device of the embodiment of the present application.
[0092] In some embodiments, the above-mentioned vehicles include but are not limited to automobiles, motorcycles, power-assisted bicycles, bicycles, power tools, etc.
[0093] Certain features of the present technology are further illustrated in the following non-limiting examples.
[0094] 1. Examples and Comparative Examples
[0095] Example 1
[0096] (Negative electrode material)
[0097] The negative electrode material of this embodiment is composed of the following components in percentage by mass: 5% pre-lithiation silicon dioxide material, 0.5% polyacrylic acid, 0.03% single-walled carbon nanotubes, and the rest is artificial graphite.
[0098] (Method for preparing negative electrode material)
[0099] The pre-lithiation silicon dioxide material, polyacrylic acid, and single-walled carbon nanotubes were stirred at a speed of 1200 rpm / min for 2 hours, and then stirred at a speed of 500 rpm / min for 1 hour to obtain the negative electrode material of this embodiment.
[0100] (Negative electrode)
[0101] The negative electrode plate of this embodiment includes a negative electrode current collector and a negative electrode material of this embodiment coated on the opposite sides of the negative electrode current collector, wherein the negative electrode current collector is a copper foil (thickness is 6 μm). The compaction density of the negative electrode material in the negative electrode plate is 1.3 g / cm 3 .
[0102] (Method for preparing negative electrode sheet)
[0103] The negative electrode material of this embodiment was added to the negative electrode solvent N-methylpyrrolidone, dispersed at a speed of 2500 rpm / min for 90 seconds three times, and the slurry was placed for 2 hours after homogenization to obtain a negative electrode slurry; then the negative electrode slurry was dispersed once more at a speed of 2500 rpm / min, coated on the negative electrode current collector, and then rolled and dried to obtain a negative electrode sheet. During the rolling process, the surface density of the negative electrode material in the negative electrode sheet was controlled to be 2.0 g / cm 2 , compacted density is 1.3g / cm 3 .
[0104] (Electrochemical Device)
[0105] The electrochemical device of this embodiment is a soft-pack battery, including a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. Among them: the negative electrode is the negative electrode sheet of this embodiment, the positive electrode sheet includes a positive electrode collector and a positive electrode material, the positive electrode collector is an aluminum foil (12 μm), and the positive electrode material includes the following components by weight: positive electrode active material LiNi 0.5 Co 0.3 Mn 0.2O2 97.6 parts, positive electrode conductive agent conductive carbon black 1.4 parts, positive electrode binder polyvinylidene fluoride 1 part, positive electrode solvent N-methyl-2-pyrrolidone 24 parts. The diaphragm is a polypropylene diaphragm. The electrolyte is a 1 mol / L LiPF6 solution, wherein the solvent is a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC), and the additives are fluoroethylene carbonate (FEC) and vinylene carbonate (VC). The mass ratio of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), fluoroethylene carbonate (FEC), and vinylene carbonate (VC) is EC:DMC:DEC:FEC:VC=0.3:0.3:0.3:0.07:0.03.
[0106] (Method for preparing electrochemical device)
[0107] The method for preparing the electrochemical device of this embodiment comprises the following steps:
[0108] (1) Preparation of positive electrode sheets: The positive electrode active material, positive electrode conductive agent, positive electrode binder and positive electrode solvent are mixed in the formulated amounts to obtain positive electrode slurry, which is then coated, dried, rolled and cut to obtain positive electrode sheets.
[0109] (2) Assembly: Assemble the positive electrode sheet, separator, negative electrode sheet and electrolyte into a soft-pack battery. After the battery is assembled, let it stand for 12 hours.
[0110] Example 2
[0111] This embodiment is basically the same as Embodiment 1, except that:
[0112] The compaction density of the negative electrode material in the negative electrode sheet is 1.5g / cm 3 .
[0113] Example 3
[0114] This embodiment is basically the same as Embodiment 1, except that:
[0115] The compaction density of the negative electrode material in the negative electrode sheet is 1.6g / cm 3 .
[0116] Example 4
[0117] This embodiment is basically the same as Embodiment 1, except that:
[0118] In the negative electrode material, the content of the single-walled carbon nanotubes is 0.05 wt %.
[0119] The compaction density of the negative electrode material in the negative electrode sheet is 1.5g / cm 3 .
[0120] Example 5
[0121] This embodiment is basically the same as Embodiment 1, except that:
[0122] In the negative electrode material, the content of single-walled carbon nanotubes is 0.07 wt %.
[0123] The compaction density of the negative electrode material in the negative electrode sheet is 1.5g / cm 3 .
[0124] Example 6
[0125] This embodiment is basically the same as Embodiment 1, except that:
[0126] In the negative electrode material, the content of polyacrylic acid is 1wt%.
[0127] The compaction density of the negative electrode material in the negative electrode sheet is 1.5g / cm 3 .
[0128] Example 7
[0129] This embodiment is basically the same as Embodiment 1, except that:
[0130] In the negative electrode material, the content of polyacrylic acid is 1.5 wt %.
[0131] The compaction density of the negative electrode material in the negative electrode sheet is 1.5g / cm 3 .
[0132] Example 8
[0133] This embodiment is basically the same as Embodiment 1, except that:
[0134] In the negative electrode material, the content of pre-lithium silicon oxide material is 0.1wt%, polyacrylic acid is 0.03wt%, and single-walled carbon nanotube is 0.002wt%.
[0135] Example 9
[0136] This embodiment is basically the same as Embodiment 1, except that:
[0137] In the negative electrode material, the content of pre-lithiation silicon oxide material is 10wt%, polyacrylic acid is 1.5wt%, and single-walled carbon nanotube is 0.07wt%.
[0138] Example 10
[0139] This embodiment is basically the same as Embodiment 1, except that:
[0140] In the negative electrode material, the content of pre-lithiation silicon oxide material is 19wt%, polyacrylic acid is 2wt%, and single-walled carbon nanotube is 0.15wt%.
[0141] Embodiment 11
[0142] This embodiment is basically the same as Embodiment 1, except that:
[0143] In the negative electrode material, the silicon material is silicon carbide.
[0144] Example 12
[0145] This embodiment is basically the same as Embodiment 1, except that:
[0146] In the negative electrode material, the silicon material is a mixture of silicon oxide and pre-magnesium silicon oxide in a mass ratio of 1:1.
[0147] Embodiment 13
[0148] This embodiment is basically the same as Embodiment 1, except that:
[0149] In the negative electrode material, the binder is a mixture of styrene-butadiene rubber (SBR) and sodium hydroxymethyl cellulose in a mass ratio of 1:1.
[0150] Embodiment 14
[0151] This embodiment is basically the same as Embodiment 1, except that:
[0152] In the negative electrode material, the binder is a mixture of sodium hydroxymethyl cellulose, styrene-butadiene rubber, and sodium polyacrylate in a mass ratio of 1:1:1.
[0153] Embodiment 15
[0154] This embodiment is basically the same as Embodiment 1, except that:
[0155] In the negative electrode material, the conductive agent is a mixture of multi-walled carbon nanotubes and carbon black (SP) in a volume ratio of 1:1.
[0156] Comparative Example 1
[0157] This comparative example is basically the same as Example 2, except that:
[0158] The negative electrode material does not contain single-walled carbon nanotubes.
[0159] Comparative Example 2
[0160] This comparative example is basically the same as Example 2, except that:
[0161] The negative electrode material does not contain polyacrylic acid.
[0162] Comparative Example 3 (compacted density is lower than the lower limit)
[0163] This comparative example is basically the same as Example 1, except that:
[0164] The compaction density of the negative electrode material in the negative electrode sheet is 1.2g / cm 3 .
[0165] Comparative Example 4 (compacted density is higher than the upper limit)
[0166] This comparative example is basically the same as Example 1, except that:
[0167] The compaction density of the negative electrode material in the negative electrode sheet is 1.8g / cm 3 .
[0168] Comparative Example 5
[0169] This comparative example is basically the same as Example 1, except that:
[0170] In the negative electrode material, the content of pre-lithiation silicon oxide material is 22wt%, polyacrylic acid is 2.2wt%, and single-walled carbon nanotube is 0.12wt%.
[0171] 2. Performance Test
[0172] Working steps for the cycle performance test of electrochemical devices:
[0173] Formation step: charge to 3.5V at 0.05C, charge to 3.85V at 0.1C; constant volume step: charge to 4.3V at 0.33C, discharge to 2.5V, charge to 3.85V at 0.33C; cycle step: cycle temperature 45℃, charge and discharge 1C / 1C.
[0174] The gram capacity test method of the negative electrode material is:
[0175] Carbon black (SP), polyacrylic acid (PAA), deionized water and single-walled carbon nanotubes (SWCNT) were mixed in a mass ratio of SP:PAA:water:SWCNT=2.8:46.67:100:20 (the total mass after mixing was 15g), and then the active material (15g) in the negative electrode material of the embodiment or comparative example was dispersed at 2500rpm for 90s three times, and the slurry was placed for no more than 2h after slurrying (if the placement time exceeded 30min, it was dispersed again at 2500rpm before coating), and then coated on the negative electrode current collector of each embodiment or comparative example, and then rolled and dried to make a negative electrode sheet. The surface density of the negative electrode sheet was controlled to be 2.0g / cm 2 , control the compaction density to 1.25g / cm 3 .
[0176] Ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), fluoroethylene carbonate (FEC) and vinylene carbonate (VC) were mixed at a mass ratio of EC:DMC:DEC:FEC:VC=0.3:0.3:0.3:0.07:0.03 to obtain an electrolyte solution.
[0177] The negative electrode, electrolyte and lithium sheet are assembled into a button cell (i.e. half-cell), and after assembly, the cell is left to stand for 6 hours for gram capacity test. The test steps are: 0.1C discharge to 0.005V, stand for 5 minutes 0.02C discharge to 0.005V, stand for 5 minutes 0.1C charge to 1.5V, and the ratio of the charge capacity to the mass of the active material is taken as the gram capacity.
[0178] The proportions of the negative electrode materials of the embodiments and comparative examples and the cycle performance of the corresponding electrochemical devices, as well as the gram capacity test results of the negative electrode materials are shown in Table 1.
[0179] Table 1 Negative electrode material ratios and performance test results of the embodiments and comparative examples
[0180]
[0181] According to Table 1:
[0182] It can be seen from the comparison of Examples 1-7 that when the silicon materials are all pre-lithium silicon oxide materials, the binders are all polyacrylic acid, the conductive agents are all single-walled carbon nanotubes, and the silicon content is all 5wt%, the binder content is 0.5wt%, the conductive agent content is 0.03wt%, and the compaction density is 1.5g / cm 3 The cycle performance is best.
[0183] It can be seen from the comparison of Examples 1-3 that, when the material selection and content of the silicon material, the binder and the conductive agent are the same, the cycle performance first increases and then decreases with the increase of the compaction density.
[0184] By comparing Examples 1, 8-10, it can be seen that when the silicon material, binder, and conductive agent are selected the same and the compaction density is the same, as the content of the silicon material increases, the content of the binder, the content of the conductive agent, and the gram capacity of the negative electrode material also increase, but the cycle capacity gradually decreases. This may be because the increase in the content of the silicon material leads to a decrease in the content of graphite in the active material, which in turn causes a decrease in the cycle performance.
[0185] By comparing Examples 1 and 11-15, it can be seen that, when the silicon material, binder, and conductive agent have the same content and the same compaction density, higher cycle performance can be obtained by using silicon nitride as the silicon material. When the conductive agent is a mixture of multi-walled carbon nanotubes and carbon black (SP) in a volume ratio of 1:1, the cycle performance is significantly reduced compared with single-walled carbon nanotubes. When the silicon material is a mixture of silicon oxide and pre-magnesium silicon oxide in a mass ratio of 1:1 and the binder is a mixture of sodium hydroxymethyl cellulose, styrene-butadiene rubber, and sodium polyacrylate in a mass ratio of 1:1:1, the cycle performance is basically equivalent to that of Example 1. When the silicon material is a mixture of silicon oxide and pre-magnesium silicon oxide in a mass ratio of 1:1, the cycle performance is slightly reduced compared with Example 1.
[0186] From the comparison of Examples 4-5 and Comparative Example 1, it can be seen that when the material selection of silicon material, binder and conductive agent is the same, the content of silicon material and binder are the same and the compaction density is the same, the cycle performance first increases and then decreases with the increase of the content of conductive agent.
[0187] By comparing Examples 6-7 and Comparative Example 2, it can be seen that when the material selection of silicon material, binder and conductive agent is the same, the content of silicon material and conductive agent is the same and the compaction density is the same, the cycle performance first increases and then decreases with the increase of the binder content.
[0188] By comparing Example 2 with Comparative Example 1, it can be seen that without adding a conductive agent, the cycle performance will be greatly reduced, from 800 cycles to 200 cycles.
[0189] By comparing Example 2 and Comparative Example 2, it can be seen that without adding a binder, the cycle performance will be greatly reduced, from 800 cycles to 500 cycles.
[0190] By comparing Example 1 and Comparative Examples 3-4, it can be seen that the negative electrode materials are the same, but the compaction density of the negative electrode sheet is not within the specified range of this application, which will lead to a decrease in cycle performance, but the decrease is limited. This may be because the silicon content is still relatively low (far less than 20%), and the increase in side reactions is limited, so the impact of the compaction density itself on the cycle performance is limited.
[0191] By comparing Example 1 and Comparative Example 5, it can be seen that the content of silicon material exceeds the scope of the present application. Even if the content of the binder and the content of the conductive agent are within the scope of the present application, the cycle performance will still be greatly reduced, but the gram capacity of the negative electrode material will increase.
[0192] In summary, the negative electrode material of the embodiment of the present application matches the type and content of the silicon material, binder and conductive agent to solve the problem of poor cycle performance of silicon-containing negative electrode plates; at the same time, the silicon material is mixed with graphite and the compaction density is optimized, which can further ensure that when the negative electrode material is used for the negative electrode plate, it has a higher gram capacity and can reduce the expansion rate of the negative electrode plate, and has excellent cycle performance.
[0193] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0194] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A negative electrode material, characterized in that: The negative electrode material comprises an active material, a binder and a conductive agent; the active material comprises a silicon material, and the mass content of the silicon material in the negative electrode material is less than 20%; The mass content of the binder in the negative electrode material is 0.01-5wt%; The mass content of the conductive agent in the negative electrode material is 0-3wt%.
2. The negative electrode material according to claim 1, characterized in that The amount of the silicon material used and the amount of the binder used conform to the relationship of formula (1), and the amount of the silicon material used and the amount of the conductive agent used conform to the relationship of formula (2): (-0.0112Csi 2 +0.3846Csi+0.1813)<Cn<(-0.0006Csi 2 +0.0555Csi+0.0106) (1), (-0.0003Csi 2 +0.0159Csi+0.0065)<Cm<(-6*10 -5 Csi 2 +0.0035Csi+0.0014) (2), Wherein, Csi is the content of silicon material in the negative electrode material, wt %; Cn is the content of binder in the negative electrode material, wt %; Cm is the content of conductive agent in the negative electrode material, wt %.
3. The negative electrode material according to claim 1 or 2, characterized in that: The active material also includes graphite; And / or, the content of the active substance in the negative electrode material is 92-99wt%.
4. The negative electrode material according to claim 1 or 2, characterized in that: The silicon material includes at least one of silicon oxide, pre-lithium silicon oxide, pre-magnesium silicon oxide, and silicon-carbon material.
5. The negative electrode material according to claim 1 or 2, characterized in that: The binder includes at least one of hydroxymethyl cellulose salt, styrene-butadiene rubber, polyacrylic acid, and polyacrylate; And / or, the conductive agent includes at least one of carbon nanotubes, carbon black, vapor-grown carbon fibers, and graphene.
6. The negative electrode material according to claim 5, characterized in that The binder is polyacrylic acid and / or polyacrylate; or, The binder is a mixture of hydroxymethyl cellulose salt, styrene butadiene rubber, polyacrylic acid or / and polyacrylic acid salt, wherein the mass ratio of hydroxymethyl cellulose salt, styrene butadiene rubber, polyacrylic acid or / and polyacrylic acid salt is (0.1-2):(0.1-3):(0.1-5).
7. The negative electrode material according to claim 5, characterized in that The hydroxymethyl cellulose salt includes at least one of sodium hydroxymethyl cellulose and lithium hydroxymethyl cellulose; And / or, the polyacrylate includes at least one of lithium polyacrylate, sodium polyacrylate, potassium polyacrylate and ammonium polyacrylate.
8. The negative electrode material according to claim 5, characterized in that The conductive agent is a mixture of carbon black and carbon nanotubes, and the mass ratio of the carbon black to the carbon nanotubes is (0.1-3): (0.1-2); And / or, the carbon nanotubes include at least one of multi-walled carbon nanotubes, few-walled carbon nanotubes, and single-walled carbon nanotubes.
9. A method for preparing a negative electrode material according to any one of claims 1 to 8, characterized in that: include: The active material, the binder and the conductive agent are mixed to obtain the negative electrode material.
10. A negative electrode plate, characterized in that: The invention comprises the negative electrode material according to any one of claims 1 to 8 or the negative electrode material prepared by the preparation method according to claim 9.
11. The negative electrode sheet according to claim 10, characterized in that: The compaction density of the negative electrode material is 1.3-1.75 g / cm 3 .
12. An electrochemical device, characterized in that: It comprises the negative electrode material as described in any one of claims 1 to 8, or the negative electrode material prepared by the preparation method as described in claim 9, or the negative electrode sheet as described in claim 10 or 11.
13. A vehicle, characterized in that: It comprises the negative electrode material as described in any one of claims 1 to 8, or the negative electrode material prepared by the preparation method of claim 9, or the negative electrode sheet as described in claim 10 or 11, or the electrochemical device as described in claim 12.